2008
DOI: 10.1007/s10620-008-0257-3
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review and Meta-Analysis of the Treatment for Barrett’s Esophagus

Abstract: As evidence-based strategies to the clinical management of Barrett's esophagus (BE) are lacking, we have carried out a systematic review and meta-analysis of all published randomized controlled trials with the aim of evaluating the value of different approaches in the treatment of BE. Searches were conducted in the databases PUBMED, EMBASE, and Cochrane Library. Thirteen randomized clinical trials that fulfilled the inclusion criteria and addressed the clinical questions of this analysis were assessed in more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 35 publications
0
25
0
3
Order By: Relevance
“…Cryotherapy has not been assessed in randomized controlled trials, and it is not currently indicated as an alternative endoscopic eradication therapy. Small randomized controlled trials using argon plasma coagulation have reported anecdotal highsuccess rates [67] . In the case of an early EA extending into the submucosal layer, surgery should be considered as the best option [29] , since in T1a context the rate of lymph node involvement is extremely low (< 3%) but the risk increases up to 20%25% when the submucosal layer is affected.…”
Section: Hgd and Intramucosal Eamentioning
confidence: 99%
“…Cryotherapy has not been assessed in randomized controlled trials, and it is not currently indicated as an alternative endoscopic eradication therapy. Small randomized controlled trials using argon plasma coagulation have reported anecdotal highsuccess rates [67] . In the case of an early EA extending into the submucosal layer, surgery should be considered as the best option [29] , since in T1a context the rate of lymph node involvement is extremely low (< 3%) but the risk increases up to 20%25% when the submucosal layer is affected.…”
Section: Hgd and Intramucosal Eamentioning
confidence: 99%
“…Furthermore, due to the lack of data, it remains unclear whether these strictures appeared only in patients with additional EMR. An indirect comparison between RFA and other endoscopic treatments such as photodynamic therapy, based on the data found in secondary literature [25,26], suggests less buried intestinal metaplasia and also less stenosis after treatment with the HALO system. Similar results of such a comparison also were presented in a conference paper in 2008 [27].…”
Section: Discussionmentioning
confidence: 99%
“…The test for heterogeneity was analyzed by Cochrane's χ 2 -test (Wang et al, 2007), and when the Higgins I 2 statistic was ≤50%, which determines the percentage of total variation across studies due to heterogeneity (Wang et al, 2009), the fixed effect model was used to pool studies; otherwise, the random effect model was used. P<0.10 was considered to be significant for heterogeneity between studies (Li et al, 2008). When three or more study arms in a same trial were encountered, the similar pairs were extracted after the comparison of one short-term arm with one 7-d arm separately.…”
Section: Discussionmentioning
confidence: 99%
“…Three of 15 trials had clear and adequate allocation concealment. The use of concealed allocation should have limited patient selection bias in the current study (Li et al, 2008). Moreover, to predict the outcome of H. pylori eradication, the potential influencing factors should be analyzed jointly, which include characteristics of the population according to the geographical location, the prevalence of infection and microbial resistance, and the lead-time of reassessment.…”
Section: Discussionmentioning
confidence: 99%